2016
DOI: 10.1016/j.micinf.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Surface expression of inhibitory (CTLA-4) and stimulatory (OX40) receptors by CD4+ regulatory T cell subsets circulating in human malaria

Abstract: Several CD4+ T cell subtypes contribute to immune homeostasis in malaria, but the markers that define the main suppressive T cell subsets induced by this infection remain largely unknown. Here we provide a detailed phenotypic characterization of immunoregulatory CD4+ T cell populations in uncomplicated human malaria. We found an increased proportion of CD4+ T cells expressing CTLA-4, OX40, GITR, TNFRII, and CD69 in acute-phase single-species infections with Plasmodium vivax, P. falciparum, or both. Such an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…In fact, an antimalarial compound with IDO-inhibitory properties was recently described (54). In this study, the plasma KT ratio and the plasma kynurenine concentration were strongly correlated with Treg activation, indirectly supporting an immune regulatory function of systemic IDO activity in vivax malaria, an infection in which Treg are known to be induced (11,14,55,56). However, it is not clear whether Treg contribute to the onset of disease by dampening or preventing the initiation of effector immune responses or whether they act to control immune-mediated pathology associated with malaria.…”
Section: P Vivax Modulation Of Ido Treg and DCsupporting
confidence: 62%
See 1 more Smart Citation
“…In fact, an antimalarial compound with IDO-inhibitory properties was recently described (54). In this study, the plasma KT ratio and the plasma kynurenine concentration were strongly correlated with Treg activation, indirectly supporting an immune regulatory function of systemic IDO activity in vivax malaria, an infection in which Treg are known to be induced (11,14,55,56). However, it is not clear whether Treg contribute to the onset of disease by dampening or preventing the initiation of effector immune responses or whether they act to control immune-mediated pathology associated with malaria.…”
Section: P Vivax Modulation Of Ido Treg and DCsupporting
confidence: 62%
“…In falciparum malaria, Treg were also activated, and this was associated with increased TNFR2 expression in severe, but not uncomplicated, malaria (57). Our observation of increased ex vivo Treg TNFR2 expression in primary P. vivax infection contrasts with a lack of increase in Treg TNFR2 expression reported in acute vivax malaria in regions where vivax malaria is endemic (55), with the latter likely to be recurrent and not primary infections. Frequent reexposure to Plasmodium spp.…”
Section: P Vivax Modulation Of Ido Treg and DCmentioning
confidence: 46%
“…Field studies in malaria-endemic Mali and Kenya, found that individuals recently infected with P. falciparum expressed PD-1 on CD4 + 26,27 and CD8 + T cells 27 , implicating this molecule in immune evasion. Similarly, an increased proportion of CD4 + T cells from individuals with acute-phase infections with P. vivax , P. falciparum , or both had increased expression of CTLA4, OX40, GITR, and CD69 28 suggesting a role for regulatory T cells in suppressing immunity to malaria and indicating potential targets of checkpoint control. Finally, T cell immunoglobulin and mucin-domain containing 3 (TIM3) expression was significantly increased on key populations of lymphocytes in P. falciparum -infected patients 29 .…”
Section: Introductionmentioning
confidence: 98%
“…OX40 signaling promotes T cell proliferation and survival, influences CD4 + T cell differentiation into T helper subsets (Walker et al, 1999 ; Murata et al, 2000 ; Soroosh et al, 2007 ; Song et al, 2008 ) and is reported to reverse CD4 + T cell hypo-responsiveness (Bansal-Pakala et al, 2001 ). While it has been previously described that OX40 is expressed on activated human and rodent CD4 T cells after a malaria blood stage infection (Zander et al, 2015 ; Goncalves-Lopes et al, 2016 ) no data had been reported on the expression of OX40 on T cells after a sporozoite/liver stage Plasmodium infection/immunization. We demonstrate in this study that after GAP-sporozoite immunization OX40 expression was observed on activated (CD44 hi ) CD4 + and CD8 + T cells in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In cytomegalovirus (CMV) vaccination studies it was found that the increase in vaccine potency can be achieved by α-OX40 treatment through the expansion of both antigen-specific CD4 + and CD8 + T cells (Panagioti et al, 2017 ). A marked upregulation of OX40 is observed on Plasmodium specific CD4 + T cells that are generated in both human and rodent malaria blood stage infections and, in rodent studies, α-OX40 treatment was shown to increase parasite-specific memory CD4 + T cells resulting in a reduced blood-stage infection (Zander et al, 2015 , 2017 ; Goncalves-Lopes et al, 2016 ). However, prior to this study the effects of OX40 treatment on immune responses induced by wsp vaccination have not been described.…”
Section: Discussionmentioning
confidence: 99%